Development and optimization of the micro-pocket fission detector - Nichols, Daniel Marc (Kansas State University, 2022)
Recent developments in advanced reactor technologies such as small modular reactors and the growing interest in microreactor technology has emphasized the need for increasing the capability of in-core neutron monitoring sensors. Next generation reactor concepts have decreased cost and complexity, while also decreasing the reactor core form factor. With these small-sized reactor cores, there is a need for smaller form-factor, and reliable sensors. Micro-Pocket Fission Detectors (MPFD) have been under development for the past decade, with the capability to detect local neutron flux within a spatially discrete pocket. Recent advancements to the technology have focused on improving the manufacturability and design of the device and to demonstrate unique use-cases for the technology. Extensive simulations were conducted to optimize detector chamber characteristics and to determine construction materials, operating characteristics and expected response for various reactor environments. New manufacturing techniques were developed to improve the repeatability of the design and allow for mass-production. During the research presented herein, MPFDs were successfully operated at a new maximum power level of 13 GW[subscript th] at TREAT, tracking neutron flux from 10¹⁴ – 10¹⁷ n cmˉ² sˉ¹. A set of 24 MPFD nodes were dispersed throughout the UWNR core providing real-time spatially-discrete three-dimensional neutron flux monitoring. The average detection efficiency for array 3 was determined to be to be (22.1 ± 1.64) x 10ˉ¹² cps/nv for pulse-mode operations, and (6.89 ± 0.25) x 10ˉ²¹ A/nv for current-mode operations, constituting a 0.129% and 19.30% detection efficiency for pulse and current mode respectively. During tests at UWNR, MPFDs were utilized to produce a rich dataset which will be used to validate code as part of the Nuclear Energy Advanced Modeling and Simulation (NEAMS) program.
Keywords: MPFD; In-core instrumentation; Radiation detector; Fission chamber; Neutron detection